The possible role of Ostertagia circumcincta, coccidiosis and dietary protein level in the development of swelling disease in Angora goat kids - Snyman, M A; Snyman, A E (Journal of the South African Veterinary Association, 2005)
A trial was carried out to investigate the possible role of Ostertagia circumcincta, coccidiosis and level of protein in the diet in the development of swelling disease in Angora goat kids. Eighty Angora goat kids were bought from 5 producers whose flocks had a history of swelling disease. These kids were kept in enclosures at Grootfontein Agricultural Development Institute near Middelburg (Eastern Cape) for the duration of the experiment. The animals received a combination of the following treatments: (a) high protein vs normal protein diet; (b) Ostertagia circumcincta infection or no O. circumcincta infection; (c) coccidial infection or no coccidial infection. Data recorded included weekly body weight, weekly total plasma protein levels (TPP), weekly faecal egg counts, weekly coccidial oocyst counts and haematology at Weeks 1, 5, 9, 13 and 16. The goats were also monitored daily for any clinical symptoms. There was no specific trend in any of the parameters measured among the different treatment groups at any stage during the experimental period. The goats were shorn during Week 10 of the experiment. On Monday 6 September 2004 (Week 12 of the study), 19 of the goats developed some subcutaneous oedema. The Saturday (4 September 2004) was rather hot (30 degrees C), followed by very cold rainy conditions (11 degrees C) on Sunday (5 September 2004). Twelve of the goats developed what can be described as little oedema, while 7 developed moderate oedema. The number of goats that developed oedema was fairly evenly distributed among the various treatment groups. As far as the specific treatments are concerned, more goats on the normal protein diet developed moderate oedema than the goats on the high protein diet. Body weights of goats that developed moderate oedema were lower throughout the experimental period than body weights of goats that developed little or no oedema, while TPP of goats that developed moderate oedema were lower from Week 5 of the study onwards. There were also no significant differences at any stage throughout the experimental period in faecal egg counts, faecal coccidial oocyst counts or any of the blood parameters between goats that developed moderate oedema, little oedema and those that did not develop any oedema. No goats developed full-blown swelling disease during the course of the experiment. It is possible that the treatments applied in this study are not inductive of the disease, or the effects of the treatments were not severe enough to induce swelling disease.